Glycaemia dynamics in gestational diabetes mellitus - Valero, Paola; Salas, Rodrigo; Pardo, Fabián; Cornejo, Marcelo; Fuentes, Gonzalo; Vega, Sofía [UNESP]; Grismaldo, Adriana; Hillebrands, Jan-Luuk; Van der Beek, Eline M.; Van Goor, Harry; Sobrevia, Luis [UNESP] (Elsevier, 2022)
Pregnant women may develop gestational diabetes mellitus (GDM), a disease of pregnancy characterised by maternal and fetal hyperglycaemia with hazardous consequences to the mother, the fetus, and the newborn. Maternal hyperglycaemia in GDM results in fetoplacental endothelial dysfunction. GDM-harmful effects result from chronic and short periods of hyperglycaemia. Thus, it is determinant to keep glycaemia within physiological ranges avoiding short but repetitive periods of hyper or hypoglycaemia. The variation of glycaemia over time is defined as ‘glycaemia dynamics’. The latter concept regards with a variety of mechanisms and environmental conditions leading to blood glucose handling. In this review we summarized the different metrics for glycaemia dynamics derived from quantitative, plane distribution, amplitude, score values, variability estimation, and time series analysis. The potential application of the derived metrics from self-monitoring of blood glucose (SMBG) and continuous glucose monitoring (CGM) in the potential alterations of pregnancy outcome in GDM are discussed.
Keywords: Endothelial dysfunction; Gestational diabetes; Glucose monitoring; pH intracellular